HIF-1 activation and inflammatory responses to hypoxiahypoxia - Shaharuddin, Shazreen; Nik Abd Rahman, Nik Mohd Afizan; Masarudin, Mas Jaffri; Alamassi, Mohammedarfat N (Embry-Riddle Aeronautical University, 2023)
Acute hypoxia is a significant physiological danger during high-altitude flying and military aircraft missions. The human brain requires a constant supply of oxygen to function properly, and is susceptible to settings with low availability of air oxygen. Hypoxia can influence inflammatory signalling, and both central and systemic responses can activate HIF pathway genes. HIFs are critical molecules that regulate inflammation andhypoxia, ensuring appropriate cell function and survival. Hypoxia is the condition in which insufficient oxygen reaches the body's tissues. It can be caused by a decrease in partial oxygen pressure (PO2) in the environment, problems with breathing and/or oxygen transport, or the inability of tissues to utilise oxygen. Different organs are hypoxic due to differences in tissue oxygen tensions, which are determined by differences in aerobic metabolism. Extremely hypoxic individuals have the most dramatic systemic and neurological adaptations to persistent hypoxia. In this review, we provide an overview of central and systemic responses to hypoxia and discuss the activation of HIF-1 pathway.